2018
DOI: 10.1007/s11095-017-2326-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Into the Effects of Tenilsetam on Markers of Neuroinflammation in GFAP-IL6 Mice

Abstract: Tenilsetam has anti-inflammatory effects evidenced by the decreased number of microglia in both the cerebellum and hippocampus, and decreased TNF-α levels in the GFAP-IL6 Tenilsetam fed animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Our study has reported that LC has the potential to downregulate the TSPO + microglia in chronic neuroinflammation. A recent study performed in the same mouse model found that the number of TSPO + cells increased in GFAP-IL6 mice and it increased even more in Tenilsetam treated mice 30 . The present study has revealed that the TSPO + microglia is significantly increased in both regions (hippocampus and cerebellum) of the brain in GFAP-IL6 normal-fed mice compared to the wild type normal-fed mice.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Our study has reported that LC has the potential to downregulate the TSPO + microglia in chronic neuroinflammation. A recent study performed in the same mouse model found that the number of TSPO + cells increased in GFAP-IL6 mice and it increased even more in Tenilsetam treated mice 30 . The present study has revealed that the TSPO + microglia is significantly increased in both regions (hippocampus and cerebellum) of the brain in GFAP-IL6 normal-fed mice compared to the wild type normal-fed mice.…”
Section: Discussionmentioning
confidence: 83%
“…The weight of the GFAP-IL6 animals was not significantly affected by diet. increased in response to injury and inflammation 30 . In order to investigate the genotype difference between the wild type and GFAP-IL6 normal food-fed mice, and to test the effect of LC on TSPO + microglia in both wild type and GFAP-IL6 mice, immunohistochemistry and stereological counting of the TSPO positive microglia/ macrophages was performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, however, the microglia phenotype of GFAP‐IL6 and GFAP‐IFN mice does differ, indicating that the cellular characteristics of microglia in these transgenic mice are defined by the specific transgene driven local environment (Figure ). In the CNS of GFAP‐IL6 mice, the number of microglia is increased (Gyengesi et al, ) and these cells show characteristic changes in their morphology similar to those observed in patients with NMOSD, such as decreased ramification and retracted processes (Figure ; Campbell et al, ; Quintana et al, ; Vallieres, Campbell, Gage, & Sawchenko, ). Microglia from GFAP‐IL6 mice have activated STAT3 in their nucleus (Campbell et al, ; Campbell et al, ; Sanz, Hofer, Unzeta, & Campbell, ), consistent with these cells mounting a direct response to IL‐6.…”
Section: The Response Of Microglia In Il‐6‐ and Ifn‐i‐mediated Neuroimentioning
confidence: 90%
“…In the GFAP-IL6 mouse model, the murine IL-6 gene is expressed by astrocytes under the transcriptional control of the glial fibrillary acidic protein (GFAP) promoter, resulting in brain-specific overexpression of IL6 and chronic low-grade neuroinflammation, characterized by microglia and astrocyte activation throughout the lifespan (Gyengesi et al, 2019). This has been demonstrated via a significant increase in Iba-1 + and TSPO + microglia and macrophages, GFAP + astroglia and neurodegeneration predominantly in the cerebellum (Campbell et al, 1993), leading to the activation of microglia (microgliosis) and astrocytes (astrocytosis) (Gyengesi et al, 2018) and a range of structural and functional neurological impairments that typify various neurodegenerative diseases (Campbell et al, 1993). Previous studies have reported that GFAP-IL6 transgenic mice display a high level of IL6 expression in the cerebellum compared with other brain regions (Campbell et al, 1993;Quintana et al, 2009).…”
Section: Introductionmentioning
confidence: 99%